SISTEM INFORMASI PEMINJAMAN MODAL USAHA TANI PADA KELOMPOK TANI MAJU BERSAMA DI KABUPATEN GORONTALO - Iswanto Mohi; Lillyan hadjaratie; tajuddin abdillah (Gorontalo State University, 2021)
Abstract Highly limited and accessible availability of capital sources for farmers has required an adjustment in the purchase of paddy farming business input with their existing capital. In other words, one of the obstacles experienced by farmers and small-scale agribusiness players to develop their business is the lack of access to capital sources. This research was aimed at designing an app which could facilitate farmers with investors in dealing startup capital in the farming issue. System development method applied prototype: 1. Communication and necessities collection, 2. Quick planning, 3. Quick design modelling, 4. Prototype making, 5. Distribution of system/software to consumers/users and feedback by using Codeigniter programming language and MySQL database. Research finding showed that the startup capital in farming loan information system could facilitate between farmer and investor. Keywords: Farming Business, Codeigniter, Prototype